2001
DOI: 10.1111/j.1600-0463.2001.tb00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry and physiology of anabolic hormones used for improvement of meat production

Abstract: A number of hormones are involved in endocrine regulation of growth. In general, these hormones enhance body protein accretion and metabolise fat stores resulting in increased lean growth rates. Most practical importance was obtained by sex hormones (oestrogens and androgens), beta-agonists and growth hormone - whether legally or illegally. Efficiency of growth promotion ranges between 0% and +20% depending on the prerequisites such as species, breed, gender, age, reproductive status, body score or feeding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 35 publications
1
67
0
7
Order By: Relevance
“…In that study, during late estrus, the frequency of profound dark cutting (pH > 6.0) was greatly increased by mounting activity, which significantly lowered the glycogen level in the longissimus muscle (Kenny and Tarrant 1988). A reduction in the tendency of heifers to cut dark in subsequent years may have been due to the use of melengesterol acetate (MGA) (Jones and Tong 1989), which suppresses estrus activity (Meyer 2001). In the data set of the present study, the MGA status of the heifers was not known; therefore, the reasons for the observed increased frequency of dark cutting in heifers in the current study were not able to be confirmed.…”
Section: Discussionmentioning
confidence: 92%
“…In that study, during late estrus, the frequency of profound dark cutting (pH > 6.0) was greatly increased by mounting activity, which significantly lowered the glycogen level in the longissimus muscle (Kenny and Tarrant 1988). A reduction in the tendency of heifers to cut dark in subsequent years may have been due to the use of melengesterol acetate (MGA) (Jones and Tong 1989), which suppresses estrus activity (Meyer 2001). In the data set of the present study, the MGA status of the heifers was not known; therefore, the reasons for the observed increased frequency of dark cutting in heifers in the current study were not able to be confirmed.…”
Section: Discussionmentioning
confidence: 92%
“…Consistent superiority of males has been widely reported, with similar trends being reported by Tawonezvi and Ward (1987). This has been attributed to hormonal differences between sexes and their resultant effects on growth (Meyer, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…The use of anabolic agents in animal husbandry is very profitable as treated animals are growing faster and exhibit a higher amount of lean meat due to nitrogen retention and a decrease in total body fat [1]. In some countries, e.g.…”
Section: Introductionmentioning
confidence: 99%